Reconstruction of a Damaged Lower Polar Artery for Kidney Transplantation Using Tubularised Donor Aorta - A. J. Vicéns-Morton; C. Callaghan; J. Olsburgh (Case Reports in Transplantation)
Introduction. Live donors, extended donor criteria, and the maximum usage of organs with anatomical variants are some of the mechanisms used to increase the number of organs available. Case. We present the case of a kidney transplant, in which the organ had an iatrogenic injury to a lower pole arterial branch during retrieval. The donor was a 35-year-old male (DCD, Maastricht III). The right kidney was accepted; it had three veins in a single cava patch and three renal arteries, the main artery with aorta patch that is 8 cm long. A small lower pole artery was sectioned during retrieval surgery at approximately 1 cm from its origin as well as a third small mid-lower pole artery. The lower pole damaged artery was reconstructed using tubularised aorta patch to a total length of 5 cm. No additional donor vessels had been sent. After construction of the tubulised aorta, E-E anastomosis to the damaged polar artery was done with interrupted 7-0 Prolene sutures. Conclusion. While the waiting list for a kidney continues to rise and we continue to have organ shortness, vascular retrieval injury should not be an absolute contraindication for transplant.